Comparative yield, yield related parameters and elemental composition of oyster mushroom (Pleurotus ostreatus) grown on different substrates: Mushroom culture - Johnnie, Christina; Seecharran, Diana; Ansari, Abdullah Adil (Mushroom Research, 2023)
This research examined the yield and nutritional content of white oyster mushrooms (Pleurotus ostreatus) cultivated on wood shaving, rice straw, sugarcane bagasse and coconut coir as substrates. Rice straw and sugarcane bagasse produced the highest yield in terms of pileus diameter, fresh and dry weight. Sugarcane bagasse produced fruiting bodies with the highest percentage of nitrogen, followed by wood shaving, rice straw and the coconut coir. Sugarcane bagasse had the highest percentage of phosphorus and the rice straw the least. Rice straw had the K content, and coconut coir the least. The yield and nutritional value of mushrooms is determined by the chemical composition of the substrate P. ostreatus produce ligninolytic enzymes that can degrade the organic compounds in the substrates into inorganic compounds that they can use for metabolic functions and as energy.